The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.esxm.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Erectile Dysfunction and Silent Myocardial Ischemia in Diabetic Patients: A Multidetector Computed Tomographic Coronary Angiographic Study

Abstract: IntroductionErectile dysfunction (ED) can precede coronary artery disease. In addition, silent myocardial ischemia (SMI) is more common in diabetic patients and is a strong predictor of cardiac events and death.AimTo evaluate the presence of SMI in patients with diabetes and ED using multidetector computed tomographic coronary angiography (MDCT-CA).MethodsThis study evaluated patients with diabetes and ED without any history of cardiac symptoms or signs. Erectile function was evaluated with the Sexual Health I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The main complications and comorbidities related to ED are schematically presented in Figure 1 and are discussed below. 17 …”
Section: The ‘Complicated Role’ Of Complications and Cofactors In The...mentioning
confidence: 99%
“…The main complications and comorbidities related to ED are schematically presented in Figure 1 and are discussed below. 17 …”
Section: The ‘Complicated Role’ Of Complications and Cofactors In The...mentioning
confidence: 99%
“…Peripheral vascular disease has been shown to be independently associated with silent CAD in several studies [11,39,45,108,110,111]. Rajagopalan et al [39] concluded that ECG Q waves, and peripheral artery disease (OR 2.134, CI 1.150-3.961; P = 0.016) were the 2 most important variables associated with high risk findings on stress SPECT, in their analysis.…”
Section: Factors Associated With Silent Coronary Artery Disease In Tymentioning
confidence: 99%
“…The presence of diabetes target organ damage has been investigated in several studies, and a higher prevalence of silent CAD was demonstrated for retinopathy [20,26,55,93,94], neuropathy [11,[95][96][97][98][99][100], and nephropathy [59,[101][102][103][104], as well as for peripheral vascular disease [105][106][107][108][109][110][111][112].…”
Section: Factors Associated With Silent Coronary Artery Disease In Tymentioning
confidence: 99%
See 1 more Smart Citation